(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2021)
The COVID-19 pandemic has meant that business and contractual relationships have been disrupted. The pandemic has also meant that there are legal liabilities owed to disruption, cancellations, or to the imposed halt of everyday life. We discuss force majeure and frustration in contract in cases where circumstances have changed due to unnatural events such as the COVID-19 pandemic and the impact of the pandemic on business interruption, and liability insurance. The scope of insurance coverage for catastrophic risks and the civil liability insurance as well as business interruption coverage are discussed and conclusions on the role of insurance in the COVID-19 pandemic are drawn, as the body of case law and the pandemic per se continues to sweep humanity in an unprecedented way.